Pendampingan Desain Studio Podcast Untuk Peningkatan Workstation Productivity Di SMKS Al-Ittihad Cianjur - Abdul Kholik; Asep Soegiarto; Dian Yusuf (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Since its introduction in 2005, podcasts have gained increasing popularity and widespread usage across various sectors. Apart from serving as a form of entertainment that shares the characteristic of proximity, similar to radio, podcasts have also emerged as an educational media, attracting a growing number of enthusiasts. The education sector has recently embraced podcasts as a tool to enhance the development of skills and abilities in podcast creation, ultimately leading to improved workstation productivity. The activities are designed based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) for media development. The implementation of these activities includes the introduction and installation of podcasting equipment, as well as providing tutorials on the usage of podcast recording software. Reflecting on the content presented, practical exercises are conducted, wherein students assume the role of operators, while teachers act as podcasters delivering subject-specific material aligned with the subjects they teach.